Features of alienation in the sermons of Imam Hussein - alhalw, wasan mansur (Al-Adab Journal, 2016)
Alienation is a term , which is derived from the Latin language, Latin noun which means transferring condominium of something to something else, or it is remotion of something. The researcher is dividing alienation of the paper into three fields:- 1- Alienation at pre-Islamic times :- They were suffering from feeling of alienation when they stood at the debris and this is clear in their poems, it is discovered through their crying , losing of their beloveds as we saw at the beginning of the famous poem of Imrua’ el-Qais. 2-Alienation at the Islamic period:- There are many types of alienation, alienation of time , of place of people and the common alienation of Homeland. 3-This paper is concerned with alienation of Imam Hussain, of some of his speeches, the researcher depended on the artistic images of the speeches and of the rhetoric style of Imam Hussain’s speech